Boehmite and stannous oxide composite material as well as one-step preparation method and application thereof
The large-pore hollow spherical boehmite@stannous oxide composite material is prepared through a one-step hydrothermal reaction, which solves the problems of high production cost and difficult waste liquid treatment in the existing technology, and achieves process simplification, cost reduction and material performance improvement. .
Patent Information
- Application Number
- CN202411286471.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2025-01-24
AI Technical Summary
The prior art requires the use of metal complexing agents and organic solvents when preparing boehmite@stannous oxide composite materials, resulting in high production costs and difficulty in handling waste liquids, while it is difficult to simplify the preparation process and maintain the specific morphological structure of the composite material.
Through one -step method, aluminum source, tin source, and urea are used as reaction raw materials, and the reaction conditions are controlled to prepare the large -hole hollow spherical Bomtestone@oxidation Asian tin composite material to avoid using metal complexes and organic solvents.
A simplified preparation process is achieved, the production cost is reduced, the pollution of waste liquid is reduced, and the hollow grading structure of the composite materials has improved its application potential in the fields of flame retardant, adsorption, and catalytic.
Smart Images

Figure CN119349612A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of boehmite, and in particular to a boehmite@tin oxide composite material and a one-step preparation method and application thereof. Background Art
[0002] Boehmite is the main component of bauxite, also known as soft water stone. It is an important chemical raw material with a unique crystal structure. It is widely used in many fields such as catalysts and carriers, papermaking fillers, inorganic flame retardants, etc. As a natural halogen-free flame retardant, boehmite has good thermal stability. During the thermal decomposition process, it decomposes to produce water vapor, absorbs heat, and plays a role in diluting the matrix and decomposing the combustible gas. On the other hand, it can produce aluminum oxide to cover the surface of the material, playing a role of heat insulation and oxygen isolation.
[0003] With the continuous deepening of research in the field of materials science, the preparation of inorganic nanomaterials with specific morphologies has also become a hot topic. Core-shell or hollow microsphere morphology can be used in the fields of catalysts, drug carriers, and environmental pollutant adsorbents due to its unique cavity structure and large specific surface area; the flower-like structure has more edges and corners. Compared with atoms on the plane, atoms on the edges and corners usually have higher activity and selectivity, so it has better application prospects in catalysis, sensing and other fields. In current research, when preparing hollow spherical boehmite, it is generally believed that surfactants or structural inducers need to be added to promote the synthesis of hollow spherical boehmite or alumina precursors.
[0004] Stannous oxide is an important material among semiconductor metal oxides and is widely used in coating materials, lithium-ion batteries, sensors and other fields. It can not only be used as a raw material for conductive coatings or semiconductor materials for manufacturing electronic components, but also as a raw material for catalysts to catalyze the reaction of organic compounds, promote the reaction, and increase the reaction rate and efficiency.
[0005] Patent CN201711225417.8 discloses a method for preparing metal-doped boehmite, by mixing a certain proportion of doped metal salt solution and aluminum source solution as precursors, using a metal chelating agent for chelation, and then solvent thermally reacting in a reactor for a certain period of time to obtain metal-doped boehmite with different morphologies. The patent prepares metal-doped boehmite by a one-step method, and the product morphology obtained by doping with different metal ions is different, indicating that the morphology structure of boehmite is determined by the regulation of the doped metal ions, and the metal ions regulate the morphology of boehmite in the form of doping into the crystal lattice, which belongs to boehmite doping material, not a composite material of metal compounds and boehmite. In addition, the patent uses sodium citrate as a metal chelating agent and an organic solvent as a synthetic solvent in the preparation process, which has a high production cost and requires waste liquid treatment.
[0006] Patent CN201210408142.2 discloses a method for preparing a nanocomposite catalyst TiO2-γ-AlOOH, wherein TiO2 is added to anhydrous ethanol, then aluminum sec-butoxide is added, heated and stirred, aged, filtered, rinsed with acetone, and dried to obtain a nanocomposite catalyst TiO2-γ-AlOOH. This patent only reflects the synthesis and preparation of γ-AlOOH from raw materials to finished products, and the finished product TiO2 is used to load γ-AlOOH. The preparation method shown is only the finished product composite stage, rather than the raw materials generating products and forming composite materials at the same stage. Organic solvents are used as synthetic solvents during the experiment, and acetone is a dangerous substance. The risk during the operation is high, and the waste solution pollutes the environment. Summary of the invention
[0007] The technical problem to be solved by the present invention is to provide a one-step method for preparing a boehmite@tin oxide composite material, wherein the boehmite matrix in the composite material is a macroporous hollow sphere, the outer shell is formed by fiber or blade structure cluster assembly, the tin source is subjected to processes such as hydrolysis to form tin oxide, and is combined at specific positions such as the fiber or blade structure edge of the boehmite matrix, and the addition of metal ions does not affect the morphological structure formation of the matrix. At the same time, the one-step hydrothermal synthesis of hollow spherical boehmite with special morphology not only simplifies the cumbersome steps of adding metal complexing agents or other additives in the prior art, but also has simple operation, short process flow, and is easy to industrialize, and the hollow hierarchical structure of the product makes it have potential application value in the fields of flame retardancy, adsorption, catalysis, etc.
[0008] The technical problem to be solved by the present invention is achieved by adopting the following technical solutions:
[0009] One of the purposes of the present invention is to provide a one-step method for preparing a boehmite@tin oxide composite material, wherein an aluminum source is dissolved in deionized water, a tin source and urea are then added, the mixture is mixed evenly, a hydrothermal reaction is performed, the mixture is cooled, washed and dried to obtain the boehmite@tin oxide composite material.
[0010] The second object of the present invention is to provide a boehmite@tin oxide composite material prepared by the aforementioned method.
[0011] The third object of the present invention is to provide the application of the boehmite@tin oxide composite material in the fields of flame retardancy, adsorption, catalysis, etc.
[0012] The beneficial effects of the present invention are as follows: the present invention uses an aluminum source, a tin source and urea as reaction raw materials, and synthesizes a boehmite@tin oxide composite material through a one-step hydrothermal reaction. The preparation method is not only simple to operate, has a short process flow, is easy to industrialize, and has good process environmental protection, avoids the use of organic solvents, reduces costs, and reduces waste liquid pollution and treatment difficulty; the boehmite in the prepared boehmite@tin oxide composite material is a macroporous hollow spherical structure, the addition of tin ions will not affect the morphology of the boehmite, and the hollow hierarchical structure of the boehmite@tin oxide composite material makes it have potential application value in the fields of flame retardancy, adsorption, catalysis, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 is the SEM image of the product obtained in Example 1;
[0014] Figure 2 is the XRD pattern of the product obtained in Example 1;
[0015] Figure 3 is the EDS diagram of the product obtained in Example 1;
[0016] Figure 4 is the SEM image of the product obtained in Example 2;
[0017] Figure 5 This is the SEM image of the product obtained in Example 3;
[0018] Figure 6 is the SEM image of the product obtained in Example 4;
[0019] Figure 7 is the SEM image of the product obtained in Example 5;
[0020] Figure 8 This is the SEM image of the product obtained in Example 6;
[0021] Fig. 9 is the SEM image of the product obtained in Example 7;
[0022] Fig.10 is the SEM image of the product obtained in Example 8;
[0023] Fig.11 is the SEM image of the product obtained in Example 9;
[0024] Fig.12 is the SEM image of the product obtained in Example 10;
[0025] Fig.13 is the SEM image of the product obtained in Example 11;
[0026] Fig.14 is the SEM image of the product obtained in Example 12;
[0027] Fig.15 This is the SEM image of the product obtained in Comparative Example 1;
[0028] Fig.16 This is the SEM image of the product obtained in Comparative Example 2;
[0029] Fig.17 This is the SEM image of the product obtained in Comparative Example 3;
[0030] Fig.18 This is the SEM image of the product obtained in Comparative Example 4. DETAILED DESCRIPTION
[0031] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further described below in conjunction with specific embodiments and diagrams.
[0032] The invention provides a one-step method for preparing a boehmite@tin oxide composite material, comprising dissolving an aluminum source in deionized water, adding a tin source and urea, mixing the mixture evenly, performing a hydrothermal reaction, cooling, washing and drying to obtain the boehmite@tin oxide composite material.
[0033] The present invention regulates the morphology and structure of the product by controlling factors such as anions in the aluminum source, hydrothermal reaction temperature and time, and the ratio of the aluminum source to the tin source and urea.
[0034] In a further technical solution, the aluminum source is at least one of aluminum sulfate, aluminum chloride, aluminum nitrate and hydrates thereof.
[0035] In a further technical solution, the tin source is at least one of stannous chloride, stannous acetate, and stannous sulfate.
[0036] In a further technical solution, the molar ratio of the aluminum source to the tin source is (10-30):1, and the molar amount of the aluminum source is Al 3+ The molar amount of tin salt is Sn 2+Preferably, the molar ratio of the aluminum source to the tin source is 20:1.
[0037] In a further technical solution, the molar ratio of the aluminum source to urea is 1:(5-15), and the molar amount of the aluminum source is Al 3+ Preferably, the molar ratio of the aluminum source to urea is 1:6.6.
[0038] In a further technical solution, the reaction temperature of the hydrothermal reaction is 100-150° C., and the reaction time is 6-24 hours.
[0039] In a further technical solution, the washing is performed with deionized water and anhydrous ethanol to remove impurities in the product.
[0040] In a further technical solution, the drying is normal pressure drying or vacuum drying. The solvent introduced by washing is removed by drying, and the drying temperature and drying time are reasonably controlled to reduce energy consumption.
[0041] The present invention also provides a boehmite@tin oxide composite material prepared by the above method.
[0042] The boehmite in the boehmite@stannous oxide composite material is a macroporous hollow spherical structure, and the stannous oxide is distributed on the edge of the fiber / blade structure on the surface of the boehmite particles.
[0043] Boehmite itself has good flame retardant properties, and its hollow macroporous structure can effectively absorb smoke produced by combustion. The stannous oxide at the edge of the structure can not only inhibit crystal growth, which is conducive to the formation of nanoparticles, but also improve the reaction activity, making the composite material have better smoke suppression performance.
[0044] The present invention also provides applications of the boehmite@tin oxide composite material in the fields of flame retardancy, adsorption, catalysis, etc.
[0045] The one-step method for synthesizing the boehmite@tin oxide composite material provided by the present invention has a product whose morphology evolution process during the hydrothermal process is divided into the following two stages:
[0046] In the first stage, as aluminum salt and urea continue to hydrolyze, Al 3+ and OH - The concentration continues to increase. When the concentrations of both reach an oversaturated state, the particles in the system rapidly nucleate to form an amorphous phase of Al(OH)3. After the Ostwald ripening process, the smaller crystalline particles in the solution continue to dissolve, and then recrystallize and precipitate on the surface of larger grains, making the originally larger grains further enlarged and finally agglomerate to form spherical particles.
[0047] In the second stage, as the reaction temperature increases, the amorphous spherical Al(OH)3 precipitate begins to dissolve, forming boehmite particles with low solubility and stable crystal form, which are deposited on the surface of the Al(OH)3 core. As the reaction time increases, the boehmite particles grow into fiber or blade structures, and one end is combined with the amorphous core. As the core continues to dissolve, the surface is assembled by fiber / blade clusters to form a hollow spherical morphology.
[0048] In the above dissolution-recrystallization process, there are a large number of OH - , making Sn 2+ Under the action of electrostatics, it adheres to the surface of the core and then hydrolyzes to form Sn(OH)2. Due to the high reaction temperature and alkaline environment, Sn(OH)2 is rapidly dehydrated to form SnO. As the core continues to dissolve, SnO eventually combines with boehmite at the edge of the fiber / blade structure, eventually forming a macroporous hollow spherical boehmite@tin oxide composite material.
[0049] Example 1
[0050] Aluminum sulfate 18hydrate was dissolved in deionized water to prepare Al 3+ The concentration of Sn is 0.0757mol / L, then anhydrous stannous chloride is added and stirred to dissolve. 2+ With Al 3+ The molar ratio of Al is 1:20, and then urea is added and stirred to dissolve. 3+ The molar ratio of urea to boehmite was 1:6.6, and the resulting mixed solution was transferred to a PTFE-lined hydrothermal reactor for hydrothermal reaction at 150°C for 24 hours. After the reaction was completed, it was naturally cooled to room temperature, washed with water and anhydrous ethanol for three times, and dried at 80°C to obtain a boehmite@tin oxide composite material.
[0051] Examples 2 to 4 and Comparative Example 1
[0052] The method of Example 1 was followed, except that the hydrothermal reaction conditions were changed, as shown in Table 1.
[0053] Table 1
[0054] Hydrothermal reaction temperature / ℃ Hydrothermal reaction time / h Product SEM picture Example 1 150 24 Figure 1 Example 2 150 6 Figure 4 Example 3 100 24 Figure 5 Example 4 100 6 Figure 6 Comparative Example 1 200 24 Fig.15
[0055] Depend on Figure 1 , Figure 4-6 It can be seen that the morphology of the products obtained in Examples 1-4 is a macroporous hollow sphere, and its surface is composed of blade / fiber structure clusters, the length of the blade / fiber is 400-700nm, and the overall diameter is 3-6μm. Fig.15 It can be seen that when the hydrothermal reaction temperature is 200°C, the obtained product is a sheet-like structure with a width of about 0.1 μm and a length of 0.8 to 1.5 μm.
[0056] from Figure 2 It can be seen that the XRD curve of the product obtained in Example 1 has strong diffraction peaks at 2θ values of 14.44°, 28.04°, 38.25°, 49.00°, etc., which are consistent with the standard spectrum of boehmite. Figure 1 The diffraction peaks appearing at 2θ values of 18.27°, 29.842, 33.16°, 37.10°, 47.68°, 62.50°, etc. are consistent with the standard spectrum of stannous oxide, so it can be considered that the product obtained in Example 1 is a boehmite @ stannous oxide composite material.
[0057] from Figure 3 It can be seen that the product obtained in Example 1 is rich in Al and O elements, and contains a small amount of Sn element. Combining the content distribution of each element, the following conclusions can be drawn:
[0058] 1. The main component of the product is boehmite, and it also contains a small amount of stannous oxide;
[0059] 2. Stannous oxide is distributed on the edge of the flake structure on the surface of the sphere.
[0060] Examples 5 to 8 and Comparative Examples 2 to 3
[0061] The method of Example 1 was followed, except that the types and quantities of the aluminum source and the tin source were changed, as shown in Table 2 for details.
[0062] Table 2
[0063]
[0064]
[0065] Note: “-” in Table 2 means no addition.
[0066] Depend on Figure 7-10 It can be seen that the morphology of the products obtained in Examples 5-8 is macroporous hollow spheres.
[0067] Depend on Fig.16 It can be seen that the morphology of the boehmite product of Comparative Example 2 is still a macroporous hollow sphere, and its surface is assembled by blade / fiber structure clusters, the length of the blade / fiber is 400-700nm, and the overall diameter is 4-7μm. Figure 1 and Fig.16 It can be found that the product obtained without adding a tin source has an obvious flaky structure on the surface and clear edge lines, while the product obtained by adding a tin source has stannous oxide particles evenly attached to the edges of the flaky structure.
[0068] Depend on Fig.17 It can be seen that the product obtained without adding an aluminum source is an irregular block formed by the aggregation of nano-scale tin particles.
[0069] Examples 9 to 12 and Comparative Example 4
[0070] The method of Example 1 is followed, except that Sn is changed 2+ With Al 3+ The ratio of Al 3+ The specific ratio of urea is shown in Table 3.
[0071] Table 3
[0072] <![CDATA[Sn 2+ With Al 3+ ratio]]> <![CDATA[Al 3+ Ratio with urea]]> Product SEM picture Example 1 1:20 1:6.6 Figure 1 Example 9 1:20 1:5 Fig.11 Example 10 1:20 1:15 Fig.12 Embodiment 11 1:10 1:6.6 Fig.13 Example 12 1:30 1:6.6 Fig.14 Comparative Example 4 1:20 1:3 Fig.18
[0073] Depend on Figure 11-14 It can be seen that the morphology of the products obtained in Examples 9-12 is macroporous hollow spheres.
[0074] Depend on Fig.18 It can be seen that the product obtained in Comparative Example 4 is spherical particles with a particle size of 0.5 to 10 μm.
[0075] The boehmite@tin oxide composite material prepared in Example 1 was mixed with B1 material to prepare a sample. The composition of B1 material used is shown in Table 4. The flame retardant and smoke suppression performance of the obtained product was tested. The results are shown in Table 5.
[0076] Oxygen index test standard is based on GB / T 2406.2-2009;
[0077] The test standard for equal mass smoke density is based on ISO 5659-2.
[0078] Table 4
[0079] name Ratio(%) EVA 20 Ethylene-vinyl acetate copolymer 10 LDPE 10 Aluminum hydroxide 60
[0080] Table 5
[0081] Test Example 1 Test Example 2 Test Example 3 Addition amount of boehmite@tin oxide composite material / part 0 1 3 Addition amount of B1 material / portion 60 59 57 Mass proportion of boehmite@tin oxide composite material / % 0 1.67 5.00 Oxygen index (3.2mm) 35.3 36.5 39.1 Equal mass smoke density (Motis 8.77g) 389 313 275
[0082] It can be seen from Table 5 that the boehmite@tin oxide composite material prepared in the present invention has good flame retardant and smoke suppression properties, and as the mass proportion of the boehmite@tin oxide composite material increases, the flame retardant and smoke suppression properties of the product are significantly improved.
[0083] The flame retardant and smoke suppression performance of the products obtained in Comparative Examples 1-4 were tested with reference to the formulation of Test Example 3. The results are shown in Table 6.
[0084] Table 6
[0085]
[0086]
[0087] It can be seen from Table 6 that the flame retardant and smoke suppression properties of the boehmite@tin oxide composite material prepared by the present invention are improved to a certain extent. The possible reason is that the composite material prepared by the present invention has a hollow structure, a large specific surface area, a large volume share under the same mass, and a more complete interaction with the resin matrix.
[0088] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A one-step method for preparing a boehmite@tin oxide composite material, characterized in that: The aluminum source is dissolved in deionized water, and then the tin source and urea are added, mixed evenly, and then hydrothermal reaction is carried out, followed by cooling, washing, and drying to obtain a boehmite@tin oxide composite material.
2. The method according to claim 1, characterized in that: The aluminum source is at least one of aluminum sulfate, aluminum chloride, aluminum nitrate and hydrates thereof.
3. The method according to claim 1, characterized in that: The tin source is at least one of stannous chloride, stannous acetate and stannous sulfate.
4. The method according to claim 1, characterized in that: The molar ratio of the aluminum source to the tin source is (10-30):1, and the molar amount of the aluminum source is Al 3+ The molar amount of tin salt is Sn 2+ Preferably, the molar ratio of the aluminum source to the tin source is 20:
1.
5. The method according to claim 1, characterized in that: The molar ratio of the aluminum source to urea is 1:(5-15), and the molar amount of the aluminum source is Al 3+ Preferably, the molar ratio of the aluminum source to urea is 1:6.
6.
6. The method according to claim 1, characterized in that: The reaction temperature of the hydrothermal reaction is 100-160° C., and the reaction time is 6-24 hours.
7. The method according to claim 1, characterized in that: The washing is washing with deionized water and anhydrous ethanol; the drying is drying at normal pressure or vacuum drying.
8. A boehmite@tin oxide composite material prepared by the method according to any one of claims 1 to 7.
9. The boehmite@tin oxide composite material according to claim 8, characterized in that: The boehmite in the boehmite@stannous oxide composite material is a macroporous hollow spherical structure, and the stannous oxide is distributed on the edge of the fiber / blade structure on the surface of the boehmite particles.
10. Use of the boehmite@tin oxide composite material according to claim 8 or 9 in the fields of flame retardancy, adsorption and catalysis.
Citation Information
Patent Citations
Nano-composite catalyst TiO2-gamma-AlOOH and preparation method as well as application thereof
CN102921398A
A metal-doped boehmite, its preparation method and application
CN107913665B